The Copper-Catalyzed C-3-Formylation of Indole CH Bonds using Tertiary Amines and Molecular Oxygen - Chen, Jianbin; Liu, Bin; Liu, Dongfang; Liu, Shan; Cheng, Jiang (Advanced synthesis & catalysis, 2012)
A copper‐catalyzed formylation reaction has been developed by employing oxygen (O2) as the clean oxidant. The CH bonds of indoles were C‐3‐formylated by tetramethylethylenediamine (TMEDA) and water (H2O; in situ formed and external added water) as the carbonyl source in moderate to good yields with good functional group tolerance. Thus, it represents a facile procedure leading to 3‐formylindoles.